An experimental investigation on Compact Graphite Iron wear behavior at 32 °C and 200 °C. (2019) - Venugopal Rao, S.; Venkata Ramana, M.; Kumar, A.C.S.
Abstract: Compact Graphite Iron (CGI) is used at various applications at elevated temperatures. This material is recently using in automobile braking system and engine cylinders. In the present study, sliding wear test on Pin-on disc tribometer was conducted on CGI. The wear behavior was studied at room temperature (32 °C) and 200 °C test against rotating hardened steel metal disc as counter face. The influence of the temperatures on abrasive wear behavior of CGI was reported. The surface of CGI pins were examined using Scanning Electron Microscopy (SEM). It was found that the pins showed lower wear rates at 200 °C temperature compared to room temperature.